Perforin-low memory CD8(+) cells are the predominant T cells in normal humans that synthesize the β-chemokine macrophage inflammatory protein-1β - Kamin-Lewis, Roberta (The National Academy of Sciences, 2001)
The synthesis of antiviral β-chemokines has joined cytolysis as a potential mechanism for the control of HIV-1 infection by CD8(+) T cells. Recent evidence suggests that these two effector functions can diverge in some individuals infected with HIV-1; however, little is known about the CD8(+) T cell subsets in normal individuals that synthesize antiviral β-chemokines. In this report, we have used mutliparameter flow cytometry to characterize the T cell subsets that secrete the antiviral β-chemokine macrophage inflammatory protein (MIP)-1β. These studies have shown: (i) CD8(+) cells are the predominant T cell subset that synthesizes MIP-1β; (ii) MIP-1β and IFN-γ are synthesized congruently in most CD8(+) T cells; however, significant numbers of these cells synthesize only one of these effector molecules; (iii) approximately 60% of the CD8(+) T cells that synthesize MIP-1β lack perforin; (iv) MIP-1β is synthesized with approximately equal frequency by CD28(+) and CD28(−) subpopulations of CD8(+) T cells; (v) MIP-1β is synthesized by three distinct CD8(+) T cell subsets defined by the expression of CD45R0 and CD62L; and (vi) MIP-1β is not synthesized in short-term cultures of naive CD8(+) T cells. These results demonstrate substantial subset heterogeneity of MIP-1β synthesis among CD8(+) T cells and suggest that these subsets should be evaluated as correlates of protective immunity against HIV-1.